The queen sings the blues politics and pathos in the poems of a gay Chinese Filipino - Baytan, Ronald (2003)
This creative dissertation is composed of two main parts: a collection of forty-seven poems entitled The Queen Sings the Blues and a creative essay entitled Politics and Pathos: Poems of a Gay Chinese Filipino. The poetry collection covers poems written between 1992 and 2000. It is composed of seven sections dealing with the following main themes: gayness, desire and Chineseness. The poems are arranged in somewhat chronologically beginning with my early gay poems "He who sleeps in my lap" and "Mama's Songs? and ending with "the cut sleeve" poems, which underscore my maturity as a writer and the flowering of my Chinese Filipino gay identity. The essay is divided into four parts: Sacred Spaces, Poetic Poses, a personal narrative on a life touched by the written Word and nurtured by many literary visitations; In Kinship, A Gathering of Voices, a discussion of the poets I admire and emulate and of the tradition of writing to which I belong; Towards a Poetics: The Making of a Queen-Poem, an attempt at fleshing out the principles of writing that I subscribe to and apply in my poetry, a modest proposition about the connection between a poem's flowering and a queen's becoming; Chinese Retellings, notes on the politics of writing as a Chinese Filipino male homosexual and the ideological impulses that fuel the creation of art; and Desire and Pathos, Politics and Poetry, a reiteration of the main themes of my poetry and the key ideas in the essay, highlighting the connection between identity and writing, between desire and sexuality, between pathos and politics. The appendices contain a discussion of the terrain of Philippine gay poetry, the status of Chinese Philippine (Gay) Literature, and the tradition of male homosexuality in China--in order to help the reader view my work in its proper context/s and to provide him/her with an overview of the literatures to which my works belong. In a way, this creative dissertation is an attempt at filling in a big gap in Philippine Gay Literature and Chinese Philippine Literature. This is one of the first few creative works dealing explicitly with gayness, Chineseness and the connection between the two. It is hoped that more writers and scholars explore the interstices between sexuality and ethnicity, identity and writing, desire and politics.